Assessment of PZT (Soft/Hard) Composites for Energy Harvesting. (25th January 2020) - Gamboa, Bryan; Bhalla, Amar; Guo, Ruyan
Abstract: This research is focused on piezoelectric energy harvesting at high pressure fields and low frequency applications. Lead Zirconate Titanate (PZT) is the primary piezoelectric evaluated with a focus on different PZT types (soft and hard). Study of piezoelectric energy harvesting has been done earlier in cantilever designs however this study concentrates on the d33 mode. Several PZT samples and geometries have been tested as well as composite structures with different PZT types. The utilization of electrodynamic test systems and simulation tools used for the evaluation of designed structure property relations. Converted power is compared among various samples and 2:2 composite structure design was found to outperform other configurations in term of electromechanical power conversion. Experimental tests produce an output power as high as 31mW at a force of 2.5kN and frequency of 10Hz. Further investigation into 2:2 composites was conducted to optimize electromechanical output power.